Sustaining the power of the Malaysian Civil Court in the division of matrimonial property: duty of full and frank disclosure - Ibrahim, Norliah (2011)
Marriage brings no effect to the spouse’s right to acquire property. However, any property acquired during the marriage is recognized as a matrimonial property if it is evidenced that the other spouse has contributed directly or indirectly in its acquisition. On that basis, once the marriage breaks up, the parties start to distinguish the ownership of the property and desire it to be returned to the original owner or to be sold and the proceeds to be divided between them. Some divorces are concluded smoothly and amicably but in other cases both parties fight over practically everything especially their rights in matrimonial property. The governing statute has in general provides a proper guideline on how the property is to be divided depending on whether the property is jointly or solely acquired by the party. Nonetheless, fair distribution is almost impossible if the parties fail to discharge a duty of full and frank disclosure of all information relevant to the case particularly the total assets, income and liabilities. Thus, the paper attempts to discuss about the duty of full and frank disclosure in dividing a matrimonial property. This will include a discussion on the power of court to make an adverse inference against the party if they fail to discharge the duty aims at sustaining fair distribution of the matrimonial property in Malaysia by referring to the relevant provisions and decided cases.